2014
DOI: 10.1063/1.4862549
|View full text |Cite
|
Sign up to set email alerts
|

Interaction potentials and thermodynamic properties of two component semiclassical plasma

Abstract: In this paper, the effective interaction potential in two component semiclassical plasma, taking into account the long-range screening and the quantum-mechanical diffraction effects at short distances, is obtained on the basis of dielectric response function method. The structural properties of the semiclassical plasma are considered. The thermodynamic characteristics (the internal energy and the equation of state) are calculated using two methods: the method of effective potentials and the method of micropote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Where: n is the number of particles in the system (Ramazanov, Moldabekov, Gabdullin, &Ismagambetova, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Where: n is the number of particles in the system (Ramazanov, Moldabekov, Gabdullin, &Ismagambetova, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In non-ideal plasmas [21][22][23], however, it is shown that the effective interaction potential and the electron pair-correlation function would not be properly represented by the Debye-Hückel theory owing to the influence of quantum and collective correlation effects. Hence, it is expected that the occurrence times for the elastic electron-ion collision in non-ideal plasmas can be quite different from those in weakly coupled plasmas due to the quantum diffraction [28] and plasma screening effects. However, the influence of quantum diffraction and plasma screening on the occurrence time in non-ideal plasmas has not been investigated as yet.…”
mentioning
confidence: 98%
“…Very recently, Ramazanov, Moldabekov, Gabdullin, and Ismagambetova [28] has obtained an extremely useful analytic expression of the effective interaction potential V RMGI (r) between plasma particles e α and e β in non-ideal plasmas taking into account the quantum diffraction, plasma screening and symmetric effects, where α and β are types of plasma particles. Based on the RMGI-micropotential model [28], the effective interaction potential V RMGI (r) between the electron (e) and the ion (i) with nuclear charge Ze in dense non-ideal plasmas including the quantum diffraction and plasma screening effects is repressed as…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…where N is the number of particles in the system (Ramazanov, 2014). The interaction potentials for different models are presented in figure 1.…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%